Minibrake : retailing in Germany vs. licensing in the U.S. - Dittmar, Frederic; Pla?tz, Roxana; Ta?ra?k, Eszter Kata; Hulsink, Willem (London : SAGE Publications Ltd, 2017)
It was in 2012 at the incubator Idea Manufactory in Budapest when Marcell, Daniel and Peter realized the potential of MiniBrake, a remote controlled brake system, which could be applied to children's bikes. The main target groups were children between the ages of 2 and 5 and their parents. MiniBrake's future looked promising, having won prize money from start-up competitions and having received positive international press coverage. In October 2014, the start-up was ready to sell this innovative product to a mass market, but could not decide where and how to start selling it. The first option was to enter Germany's market under the MiniBrake brand and rely on specialised bicycle stores selling it. The second option was to license MiniBrake's technology to an established player in the U.S. who in turn would market and sell the brake under its own brand name.The case covers the German and U.S. bicycle markets and explains the selection criteria for MiniBrake. The risks and opportunities of direct selling through retailers and of licensing are evaluated. It also addresses the question regarding how an unknown, foreign start-up can establish trust and convince consumers of a product that is close to consumers' hearts (to protect children from accidents).
Originally Published InDittmar, F., Pla?tz, R., Ta?ra?k, E. K., & Hulsink, W. (2014). MiniBrake: Retailing in Germany vs. licensing in the U.S. Rotterdam, Netherlands: Rotterdam School of Management, Erasmus University.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Minibrake -- Case studies; Business planning -- Case studies; Globalization -- Case studies